The Making of Modern Japan - Jansen, Marius B. (The Belknap Press of Harvard University Press, 2000)
A sweeping narrative history of Japan from the Battle of Sekigahara (1600) through the twentieth century, exploring the social, political, economic, and cultural transformations that shaped modern Japan.